2011
DOI: 10.1631/jzus.b1100013
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional evaluation of upper anterior alveolar bone dehiscence after incisor retraction and intrusion in adult patients with bimaxillary protrusion malocclusion

Abstract: Abstract:Objective: The purpose of this study was to evaluate three-dimensional (3D) dehiscence of upper anterior alveolar bone during incisor retraction and intrusion in adult patients with maximum anchorage. Methods: Twenty adult patients with bimaxillary dentoalveolar protrusion had the four first premolars extracted. Miniscrews were placed to provide maximum anchorage for upper incisor retraction and intrusion. A computed tomography (CT) scan was performed after placement of the miniscrews and treatment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 35 publications
2
16
1
2
Order By: Relevance
“…At the lateral incisor sites, the fenestration rate even reached 42.6%. In the present study, the incidence of fenestration is higher than that reported in the edentulous anterior maxilla, and this might be explained by differences in the alveolar bone profile, which exist between Asians and other races . The average RA measured in the anterior maxillary area was 125.76 ± 7.44°, which was bigger than that in Chan's study.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…At the lateral incisor sites, the fenestration rate even reached 42.6%. In the present study, the incidence of fenestration is higher than that reported in the edentulous anterior maxilla, and this might be explained by differences in the alveolar bone profile, which exist between Asians and other races . The average RA measured in the anterior maxillary area was 125.76 ± 7.44°, which was bigger than that in Chan's study.…”
Section: Discussioncontrasting
confidence: 81%
“…The initial facial bone profile cannot be ignored, especially for Asians, because of the differences in the alveolar bone profile among different races . The protrusion of the anterior maxilla is commonly observed in Asians, while protrusion of the anterior maxilla is less prevalent in Europeans . Given these characteristics of the facial bone profile in the anterior maxilla, the prevalence of fenestrations and/or dehiscences may be higher if the implants are positioned in a restoration‐driven position.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason 3-D evaluation is required which could provide 3 dimensional displacement for dentoalveolar changes [22]. It was found that width of the alveolar bone irt maxillary anteriors had improved to a considerable level in the corticotomy group, which may be attributed to the osteoinductive graft material added during the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…These results could be used in forecasting the morphology of the mandibular posterior tooth-alveolar bone complex in clinical treatment. The inclination of molars, average thickness of the cortical bone, and the height of the mandibular bone can be obtained only by CBCT (Wang et al, 2012) or spiral CT (Guo et al, 2011), while the FHI can be obtained using cephalometric film, which is cheaper and easier to acquire in the clinic. The tooth-alveolar complex morphology of patients may be approximated by doctors by assessing the FHI in cephalometric film.…”
Section: Discussionmentioning
confidence: 99%